The Effect of Converting a Conventional Tractor into a Hybrid Drive Tractor Using the ECMS Method on Fuel Consumption and Emissions - Ozturk, Mirac; Sandalci, Tarkan; Buyuk, Cihan; Guclu, Mustafa; Karagoz, Yasin (WILEY, 2024)
In recent years, the implementation of Tier 5 emission regulations for tractors has compelled manufacturers to conduct new research. Additionally, the process of hybridization has impacted the agricultural vehicle industry. This study focuses on the design and implementation of an energy management strategy (EMS) for a diesel-electric hybrid electric agricultural vehicle, based on real-time optimization. Tractor drive systems, including both conventional and hybrid options, were introduced. Simulations were performed to compare fuel consumption and CO2 emissions between the two types of tractors. The data shows that hybrid vehicles produce 8.93% less CO2 than conventional vehicles. Furthermore, the fuel consumption of the tractor decreased from 1,880.2 to 1,712.5 g/km under hybrid operating conditions.
Keywords: Energy & Fuels; Nuclear Science & Technology